Contrast-enhanced echocardiographic diagnosis of benign and malignant cardiac tumors and its correlation with pathology - Yang, Zihao; Niu, Yicui; Ma, Hui; Gong, Wenqing; Yu, Lu; Liu, Liwen; Zheng, Minjuan (Frontiers in Cardiovascular Medicine, 2023)
Background This study aimed to explore the diagnostic value of contrast-enhanced echocardiography (CEE) in benign and malignant cardiac tumors and detect the correlation of CEE parameters and immunohistochemistry (IHC) markers. Methods The data of 44 patients with cardiac tumors confirmed by pathology were reviewed. Lesions were examined before surgery using transthoracic echocardiography (TTE) and CEE with time-intensity curve analysis. The expression of CD31, VEGF and Ki67 was measured by IHC staining. Microvessel density (MVD) was quantified via IHC for CD31. The clinical variables, TTE, CEE and IHC parameters were compared between benign and malignant cardiac tumors. Receiver operating characteristic curve were used to analyze the value of factors in predicting malignant cardiac tumors. The correlation between CEE and IHC parameters was analyzed. Results Among 44 cardiac tumors, 34 were benign and 10 were malignant. There were significant differences in the TTE parameters (pericardial effusion, tumor boundary, diameter, basal width), CEE parameters (tumor peak intensity (TPI), peak intensity ratio of tumor to myocardium (TPI/MPI), area under time-intensity curve (AUTIC)) and IHC parameters (Ki67, MVD, CD31, VEGF) between the benign and malignant tumor groups (all P < 0.05). Receiver operating characteristic curve analysis showed that the CEE and IHC parameters had diagnostic value in malignant cardiac tumors. There was a correlation between TPI/MPI and Ki67 (r = 0.62), AUTIC and Ki67 (r = 0.50), and AUTIC and CD31 (r = 0.56). Conclusion TTE and CEE parameters were different between benign and malignant cardiac tumors. CEE is helpful to differentiate the properties of cardiac tumors. There is a correlation between CEE parameters and IHC markers. AUTIC and TPI/MPI can reflect the proliferation and invasion of tumors.